Incapacitation : Penal Confinement and the Restraint of Crime. - Zimring, Franklin (Studies in crime and public policy Incapacitation, 1997)
An assessment of incapacitation in which the authors expose the increasing reliance on restraint to justify imprisonment, analyse the existing theoretical literature and empirical research on incapacitation's effects, and explore the links between incapacitation and criminal justice policy. In the STUDIES IN CRIME AND PUBLIC POLICY series.